Are long working hours associated with weight‐related outcomes? A meta‐analysis of observational studies. (8th December 2019) - Zhu, Yi; Liu, Jianxin; Jiang, Heng; Brown, Tracey J.; Tian, Qingfeng; Yang, Yudi; Wang, Chao; Xu, Hongbin; Liu, Junan; Gan, Yong; Lu, Zuxun
Summary: The relationship between long working hours and body weight outcomes remains inconclusive; thus, we conducted a meta‐analysis to assess the effect of long working hours on weight‐related outcomes. PubMed and Embase databases were searched from their inception to June 2019. A random‐effects model was used to assess the pooled odds ratio (OR) and corresponding confidence interval (CI). Subgroup analyses and sensitivity analyses were conducted to explore sources of heterogeneity. Publication bias was evaluated by the Begg's and Egger's tests. A total of 29 articles involving 374 863 participants were included. The pooled OR of long working hours on weight‐related outcomes was 1.13 (95% CI, 1.07‐1.19). In subgroup analysis stratified by definition of outcomes, the pooled ORs of long working hours on "weight gain/BMI increase, " "BMI ≥ 25 kg/m 2, " and "BMI ≥ 30 kg/m 2 " were 1.19 (95% CI, 1.02‐1.40), 1.07 (95% CI, 1.00‐1.14), and 1.23 (95% CI, 1.09‐1.39), respectively. We found evidence of publication bias, but correction for this bias using the trim‐and‐fill method did not alter the combined OR substantially. There was evidence to suggest that long working hours are associated with adverse weight‐related outcomes. Preventative interventions such as improved flexibility and healthy working schedules should be established for employees.